Working for women’s rights in Bangladesh - Hasan, Md. Mahmudul (Bangladesh Institute of Islamic Thought (BIIT), 2016)
There is no denying that women in many societies suffer from multiple layers of discriminations and social exclusion, and that the patriarchal social structure aggravates their susceptibility to various forms of oppression and abuse. Men have enjoyed various privileges at the expense of women’s rights and wellbeing. Whenever challenged, custodians of gender-based inequalities have used social mythologies, and sometimes pseudo-religious arguments, to facilitate and sustain the complex structure of gender stereotypes and to defend their privileges, and thus to perpetuate their domination over women. As a result, as far as gender relations are concerned, especially in Muslim cultural contexts, religion and patriarchy seem enmeshed and inseparable because of misuse and wrong interpretations or misapplications of Islamic religious texts. However, people of good will and sound judgment and intellectuals with substantial socio-cultural knowledge and Islamic scholarship have said it over and over again that the religion of Islam is a means of, and not an impediment to, women’s liberation and empowerment.